Income Distribution of People of Retirement Age in Japan - Yamada, Atsuhiro (Journal of Income Distribution®, 2007)
This article examines inequality and poverty among older people in Japan. It compares Japan with that of a sample of other OECD countries. Provisions within the social insurance system that enable old-age pensioners to work and draw incomes from labor explain some of the inequality and poverty that is seen in Japan. So, too, do the low rate of take up of social assistance, the low level of benefits available from the first tier pension, the uneven coverage of second-tier pensions, the lack of progressiveness of the income tax system and the fact older people live in multi-generational households whilst others live alone.